Multisite Attenuated Intracellular Recordings by Extracellular Multielectrode Arrays, a Perspective - Spira, Micha E.; Shmoel, Nava; Huang, Shun-Ho M.; Erez, Hadas (Frontiers in Neuroscience, 2018)
Multielectrode arrays (MEA) are used extensively for basic and applied electrophysiological research of neuronal- and cardiomyocyte-networks. Whereas immense progress has been made in realizing sophisticated MEA platforms of thousands of addressable, high-density, small diameter, low impedance sensors, the quality of the interfaces formed between excitable cells and classical planar sensor has not improved. As a consequence in vitro and in vivo MEA are "blind" to the rich and important "landscape" of sub-threshold synaptic potentials generated by individual neurons. Disregarding this essential fraction of network signaling repertoire has become the standard and almost the "scientific ideology" of MEA users. To overcome the inherent limitations of substrate integrated planar MEA platforms that only record extracellular field potentials, a number of laboratories have developed in vitro MEA for intracellular recordings. Most of these novel devices use vertical nano-rods or nano-wires that penetrate the plasma membrane of cultured cells and record the electrophysiological signaling in a manner similar to sharp intracellular microelectrodes. In parallel, our laboratory began to develop a bioinspired approach in-which cell biological energy resources are harnessed to self-force a cell into intimate contact with extracellular gold mushroom-shaped microelectrodes to record attenuated synaptic- and action-potentials with characteristic features of intracellular recordings. Here we describe some of the experiments that helped evolve the approach and elaborate on the biophysical principles that make it possible to record intracellular potentials by an array of extracellular electrode. We illustrate the qualities and limitations of the method and discuss prospects for further improvement of this technology.